Habitual physical activity minimizes healthcare costs resulting from comorbidities among adults with cardiovascular diseases: Physical activity minimizes healthcare costs - Araujo, Monique Yndawe Castanho [UNESP]; Kokubun, Eduardo [UNESP]; Norberto, Maria Carolina Castanho Saes [UNESP]; Bento, André Lucas Servo [UNESP]; Turi-Lynch, Bruna Camilo; Codogno, Jamile Sanches [UNESP] (Elsevier, 2023)
Background: Habitual physical activity (HPA) can be used as a non-pharmacological strategy to prevent and control chronic diseases, as well as playing a role in minimizing healthcare costs. Objective: To verify the impact of HPA on healthcare costs at different levels of care, over 24 months, in an adult population with cardiovascular diseases (CVD), including individuals with or without comorbidities. Methods: Two-hundred and seventy-eight adults with CVD, aged between 30 and 65 years, participated in the study. Information on healthcare costs was obtained from medical records and included primary, secondary, and tertiary levels. Comorbidities such as diabetes, dyslipidemia, arterial hypertension, and obesity were registered. HPA was measured using the Baecke questionnaire. Comparisons between groups were performed using Student's t (<P75 HPA and ≥P75HPA) and Mann-Whitney (YES and NO for presence of comorbidities) tests. Quantile regression was used to measure the impact of diseases and confounding variables on healthcare costs. Statistical significance was set at <0.05. Results: The presence of comorbidities increased healthcare costs (p<0.05). HPA provided savings ranging from US$ 22.5/24 months to US$ 63.9/24 months with primary healthcare services, regardless of the presence of comorbidities. Conclusion: Considering adults with CVD, HPA significantly minimizes healthcare costs in the primary care in Brazil, even in the presence of comorbidities, such as diabetes, dyslipidemia, arterial hypertension, and obesity.
Keywords: Brazilian national health system; Exercise; Obesity; Primary health care